Adjustment Costs and Factor Demand: New Evidence from Firms' Real Estate. Issue 633 (29th July 2020) - Bergeaud, Antonin; Ray, Simon
Abstract: We study corporate real estate frictions and their effect on firm dynamics and labour demand. We build and simulate a general equilibrium model with heterogeneous firms that predicts the response of firms to a productivity shock in the presence of fixed adjustment costs on real estate. Using a large firm-level database merged with local real estate prices, we then exploit variations in the tax on capital gains to document a causal effect of adjustment costs on firms' labour demand and derive new results on the causes and implications of firms' local relocation.